SINGLE PARENT ROLE IN THE FAMILY (CASE STUDY: WOMEN AS HEADS OF HOUSEHOLD IN NAGARI DUSUN TANGAH DISTRICT SANGIR BATANG HARI REGENCY SOLOK SELATAN) - Heskurniati, Heskurniati; Elvawati, Elvawati; Fitlayeni, Rinel (Pendidikan Sosiologi, 2014)
This research is motivated presence of 102 households were headed by women in Nagari village Tangah and most of the women take on the role as a father and a mother. This study aims to describe the role of the mother as heads of household in Nagari Dusun Tangah Subdistrict Sangir BatangÂ  Hari Regency Solok Selatan.The theory used is Structural Functional Theory Talcot Parsons. This research uses a qualitative approach with descriptive type. The sampling technique used purposive sampling the number of informants as many as 10 people. Types of primary and secondary data. The collection of data through observation, interviews, and documentation. While the data analysis is data reduction, data presentation, and verification (conclusion).Based on the analysis of data, it can be concluded (1) views of economic life, the mother can be a good and responsible role became the backbone of the entire family and take care of household affairs. This mother lived well with any efforts to achieve the welfare of the family and to meet the needs of the family. In addition to the children who have to work, the childs mother also assist in meeting the economic needs of their families. (2) the childs education, the mother is able to educate, guide with affection, attention, and has advised such principle gives freedom, and being open in the family. So that the mother is able to deliver the children achieve higher levels of education in achieving his goal without a father figure. (3) the mothers social life can still play an active role in participating in the activities of community organizations to create a harmony of living together. This can be seen by busy mom taking care of the household can divide the time to maintain the balance of rights and obligations in accordance with the role in addition to the childs mother also includes activities such as youth clubs which is the activity of youth organizations. Then it implies that the mother and child to take part in the live progress of society so as to create harmony of living together.